Augmented Reality Edugame Ayo Cintai Lingkungan Sebagai Media Pembelajaran Siswa Sekolah Dasar - Purnomo, Bashid Hery, Endah Sudarmilah, S.T., M.Eng (2015)
Mobile devices have a variety of applications on it, such as mobile learning. The development of mobile learning in Indonesia by Ambient Insight in 2012 - 2017 is expected to be able to penetrate the top five in Asia (Adkins, 2013). Therefore, the author would like to take advantage of the development of mobile learning in Indonesia to create applications "Augmented Reality (AR) edugame Ayo cintai lingkungan sebagai media pembelajaran siswa sekolah dasar" This application development through several stages ranging from needs analysis to report writing. AR application Eduagme has five main menu is the menu come to learn, marker menu, menu information, menu start, and exit the menu. The usefulness of the menu let's learn that for student learning materials and the start menu as a game with the theme let students love the environment by using the marker to bring up the 3D object. This application has been tested in SDIT Muhammadiyah Al-Kautsar Kartasura. Based on the data obtained after the trial, obtained several conclusions, two of which are 96% of students stated this application helps students in learning especially regarding the environment and 97% of students stated that these applications can increase the desire to learn.